(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background : Apart from the connections between anatomical structures, any communication between the root canal space and the external tooth surface is considered as perforation . Aim : In this study, finite element analysis (FEA) was used to evaluate the stress distributions in simulated mandibular molar teeth with various iatrogenic root perforation (IRP) types after reparation with Biodentine, mineral trioxide aggregate (MTA) and Endocem Zr. Material Method : An extracted human mandibular molar tooth was scanned using micro-CT device, and solid model was created. Then, four different IRPs (furcation perforation, strip perforation, coronal perforation and lateral root perforation) and three different repair materials (MTA and Biodentine, Endocem Zr) were simulated on the model. Consequently, a total of seventeen experimental models were designed. An oblique force of 300 N angled at 45° to the occlusal plane was simulated. Evaluations of von Mises stress were carried out in the perforated regions. Results : The overall maximum stress in the sound tooth model was observed to be 109.83 MPa followed by (CP/UR) model which was 108.4 MPa, which was 106.92 MPa, (LRP/E) which was 91.63 MPa and the least was observed in the (FP/UR) which was 82.085 MPa. Conclusion : The use of MTA and Biodentine may reduce the risk of potentially harmful stresses in root perforation regions.